2001
DOI: 10.1002/1097-0142(20010225)93:1<8::aid-cncr9001>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Papanicolaou smear sensitivity for the detection of adenocarcinoma of the cervix

Abstract: BACKGROUND Papanicolaou smear sensitivity for cervical adenocarcinoma (CVCA) is not well established. Also uncertain are the relative contributions to falsely negative diagnoses of sampling, screening, and interpretive errors. METHODS Papanicolaou smears were identified from all patients at our institutions with biopsy‐proven cervical adenocarcinoma from 1988–1998. All available negative and unsatisfactory smears were reviewed. RESULTS Of 49 patients with CVCA, 66 smears initially diagnosed as negative and 4 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
3
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 23 publications
3
58
3
3
Order By: Relevance
“…Our data showing that 10 of the 12 women had a normal Pap smear within 3 years before the diagnosis of invasive disease may support the hypothesis of a rapid-onset carcinoma. On the other hand, as the sensitivity of a Pap smear for the detection of cervical adenocarcinomas is very low (Krane et al, 2001), the rapid-onset hypothesis may not apply to our cases.…”
Section: Discussionmentioning
confidence: 69%
“…Our data showing that 10 of the 12 women had a normal Pap smear within 3 years before the diagnosis of invasive disease may support the hypothesis of a rapid-onset carcinoma. On the other hand, as the sensitivity of a Pap smear for the detection of cervical adenocarcinomas is very low (Krane et al, 2001), the rapid-onset hypothesis may not apply to our cases.…”
Section: Discussionmentioning
confidence: 69%
“…18 The sensitivity of the Pap smear for detecting cervical adenocarcinoma is believed to range from 45% to 76%, with a false-negative rate of 50%. 19 Krane et al reported a sensitivity in the range of 45% to 76% for the detection of cervical adenocarcinomas, 19 whereas Boddington et al described a sensitivity range of 52% to 87% in a similar patient population. 20 Costa et al included Pap smears from patients with adenocarcinomas of both cervical and endometrial origin and demonstrated a sensitivity of 88%, but many patients in their study presented at an advanced stage of disease.…”
mentioning
confidence: 99%
“…For invasive endocervical adenocarcinoma, the false-negative rate of preceding cytologic examination was found to range from 45 to 74%, with about 20% being due to interpretation errors. 13 Suffice it to say that cytology alone is significantly less sensitive for glandular, as opposed to squamous lesions, and that education and experience is required to achieve best detection sensitivity. The cytologic criteria for the diagnosis of AIS were not well documented even as late as the first edition of the Bethesda System in 1988, 14 in which it was subsumed under the category of 'glandular atypia'.…”
Section: Endocervical Neoplasia: General Featuresmentioning
confidence: 99%
“…Fortunately, this appears to have occurred as recent data suggests that up to 80% of women having either AIS or invasive endocervical adenocarcinoma will have an abnormal cervical cytology specimen ranging from at least 'atypical' (for an incomplete, but compelling morphologic pattern) to a more specific interpretation. 13 In addition, the prevalence of AIS in registry data is increasing at a greater rate than are the precursor squamous lesions (sevenfold increase in SEER data in the past 20 years). 16 This increase is almost certainly due to a compilation of the factors noted above, including improved sampling devices, proper sampling technique, introduction of liquid-based cytology preparation allowing for improved sample preservation and presentation, and finally from better recognition of the cytologic features of glandular neoplasia.…”
Section: Endocervical Neoplasia: General Featuresmentioning
confidence: 99%